Younger hanging wall rocks along the Vaikrita Thrust of the High Himalaya: A model based on inversion tectonics - Dubey, Ashok K; Bhakuni, Surendra S (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 129